2016
DOI: 10.1016/j.tips.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin as a Therapeutic Target in Inflammatory Disease

Abstract: Members of the tristetraprolin (TTP) family of RNA binding proteins are found in all major eukaryotic groups. Family members from plants through humans can bind AU-rich elements in target mRNAs with high affinity. In mammalian cells, these proteins then promote deadenylation and decay of target transcripts. Four such proteins are found in the mouse, of which the best studied is TTP. When its gene is disrupted in the mouse, the animals develop a severe syndrome of arthritis, autoimmunity, cachexia, dermatitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 47 publications
0
67
0
Order By: Relevance
“…By contrast, suppressing MCPIP1 and roquin 1 activity may be a novel strategy for enhancing cancer immunotherapy or responses to vaccines. Recent studies with a mouse model of regulated TTP overexpression demonstrated a protective effect against several models of immune and inflammatory disease, supporting the potential role of TTP as a therapeutic target 93,94 .…”
Section: Associated Diseases and Therapeutic Potentialmentioning
confidence: 84%
“…By contrast, suppressing MCPIP1 and roquin 1 activity may be a novel strategy for enhancing cancer immunotherapy or responses to vaccines. Recent studies with a mouse model of regulated TTP overexpression demonstrated a protective effect against several models of immune and inflammatory disease, supporting the potential role of TTP as a therapeutic target 93,94 .…”
Section: Associated Diseases and Therapeutic Potentialmentioning
confidence: 84%
“…Consistent with such a function, in vitro studies suggest ZPF36 regulates the expression of T-cell-derived cytokines, including IL-2, IFN-γ and IL-17, that mediate lymphocyte homeostasis, microbial response, and inflammation (Lee et al 2012; Ogilvie et al 2009; 2005). The landscape of ZFP36 targets beyond these limited cases in T-cells is unknown, but will be the key to understanding its emerging roles in inflammation, autoimmunity, and malignant cell growth (Patial and Blackshear 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This short motif in human TTP was found to interact directly with the human CNOT1 protein (7), and a crystal structure of this interaction demonstrated key residues in the TTP C terminus that have been conserved throughout eukaryotic evolution. Since CNOT1 is a component of the CCR4-NOT complex, a multiprotein complex that contains two 3=-to-5= exonucleases, or deadenylases, this provided an attractive model for the activity of TTP and its family members: after binding to mRNA through the TZF domain, the C-terminal domain would recruit the CCR4-NOT complex to the targeted mRNA, resulting in its accelerated deadenylation and ultimate decay (7,40).…”
Section: Discussionmentioning
confidence: 99%